PENGARUH BAHAN ATAP KANDANG DAN STRAIN TERHADAP PENAMPILAN AYAM PEDAGING - ASTININGSIH, N. K. (Majalah Ilmiah Peternakan; Vol 7 No 2 (2004), 2012)
An experiment was carried out to study the effect of roof materials and strain on broiler performance, located at Dajan Peken Village, Tabanan region of Bali, about 50 m above sea level. A completely Design (CRD) with factorial arrangement 2 x 2 and three replicates was used. Each replicate constained or four birds. The primary factor were coconut leaf roof (K1) and galvanised iron roof (K2), while the secondary factor were strain of CP.707 (Sl) and MF.202 (S2) respectively. Feed in mash form was offered ad libitum. Result of this experiment showed that there were no significant interaction between roof and strain on broiler performance (P>0,05). There were significantly higher body weight gains in K1 as compared to K2 (P<0,05), but there were no significant differences of strain (P>0,05) and feed and water consumption (P>0,05). It is concluded that broilers housed under coconut leaf roof had a better performance compared to birds housed under galvanized iron.